Isolation and Characterization of Protease-Producing Thermophilic Bacteria from Padang Dama Hot Spring, Solok, Indonesia - Mellanie Alia Putri; Anthoni Agustien; Yetti Marlida; Feskaharny Alamsjah (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to isolate, screen, and partially characterize protease-producing thermophilic bacteria from the Padang Dama hot spring, Solok, Indonesia. The main issue addressed in this study is the limited information regarding thermophilic bacteria capable of producing protease enzymes from this geothermal environment, despite their potential use in industrial processes requiring stable enzymes. Isolation was carried out using Nutrient Agar followed by incubation at 50 °C for 24 hours. Screening of protease activity was performed using Skim Milk Agar based on clear zone formation, and the proteolytic index (PI) was calculated to evaluate enzyme activity. Selected isolates were further characterized through macroscopic, microscopic, and biochemical analyses. The results showed that three isolates exhibited proteolytic activity, with isolate TUA-109 showing the highest proteolytic index, indicating superior enzymatic potential compared to other isolates. Partial characterization revealed that isolate TUA-109 is a Gram-negative, rod-shaped bacterium with positive catalase activity and motility, which are important traits supporting its adaptability and potential for enzyme production under extreme conditions. These findings highlight the potential of thermophilic bacteria from the Padang Dama hot spring as sources of protease enzymes, with isolate TUA-109 identified as a promising candidate for further investigation, particularly for industrial enzyme production. Future studies are recommended to optimize enzyme production and evaluate its application in industrial processes.